Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.3389/fncir.2012.00119
|View full text |Cite
|
Sign up to set email alerts
|

Frequency discrimination and stimulus deviance in the inferior colliculus and cochlear nucleus

Abstract: Auditory neurons that exhibit stimulus-specific adaptation (SSA) decrease their response to common tones while retaining responsiveness to rare ones. We recorded single-unit responses from the inferior colliculus (IC) where SSA is known to occur and we explored for the first time SSA in the cochlear nucleus (CN) of rats. We assessed an important functional outcome of SSA, the extent to which frequency discriminability depends on sensory context. For this purpose, pure tones were presented in an oddball sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 92 publications
5
47
1
Order By: Relevance
“…The existence of consecutive gain controls over SSA in diverse auditory nuclei (IC and MGB, so far) suggests the existence of successive hierarchical levels of processing through the auditory system that would allow the reduction of redundant information. If SSA is generated in the IC (Malmierca et al ; Ayala & Malmierca, ; Ayala et al ), the first important GABAergic modulation will occur at this lowest level and will require additional adjustments as SSA is propagated up the auditory pathway through the MGB. The rat MGB contains one‐fifth of the number of neurons present in the IC (Kulesza et al ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The existence of consecutive gain controls over SSA in diverse auditory nuclei (IC and MGB, so far) suggests the existence of successive hierarchical levels of processing through the auditory system that would allow the reduction of redundant information. If SSA is generated in the IC (Malmierca et al ; Ayala & Malmierca, ; Ayala et al ), the first important GABAergic modulation will occur at this lowest level and will require additional adjustments as SSA is propagated up the auditory pathway through the MGB. The rat MGB contains one‐fifth of the number of neurons present in the IC (Kulesza et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Each frequency in the pair was always presented at the same sound level. Stimuli presented in an oddball paradigm were similar to those used to record mismatch negativity responses in human (Näätänen, ) and SSA responses in animal (Ulanovsky et al , ; Malmierca et al ; Antunes et al ; Duque et al ; Ayala et al ; Richardson et al ) studies. Briefly, 300 stimuli containing both frequencies were presented in a probabilistic manner: one frequency ( f 1 ) presented as a standard sound (90% of occurrence) was interspersed randomly with a second deviant (10% of occurrence) stimulus frequency ( f 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…Ma et al (2002) have shown a role for presynaptic GABA B receptors. Studies using microiontophoresis in vivo have demonstrated that both GABA and glycine inhibit IC neurons in several species (LeBeau et al, 1996;Palombi and Caspary, 1996a;Vaughn et al, 1996), including rat (Faingold et al, 1989(Faingold et al, , 1991Pérez-Gonzalez et al, 2012;Pérez-Gonzalez and Malmierca, 2012). Rat IC neurons also possess NMDA and AMPA receptors (Petralia and Wenthold, 1992;Ishii et al, 1993;Petralia et al, 1994;Gaza and Ribak, 1997;Caicedo and Eybalin, 1999;Schmid et al, 2001).…”
Section: Neurochemistry and Electrophysiological Responses And Functimentioning
confidence: 96%
“…In the brainstem, SSA has been recently explored in the ventral and dorsal cochlear nucleus of the rat and the results suggest that all cochlear nucleus neurons tested lack SSA (Ayala et al, 2012). Thus, the IC is the earliest center where SSA has been described (Malmierca et al, 2009a), although it remains to be tested whether or not other brainstem nuclei located in between the cochlear nucleus and IC show some degree of SSA.…”
Section: Stimulus-specific Adaptation: a Neural Mechanism For Detectimentioning
confidence: 99%